A collaborative learning approach and its evaluation - Ishitani, Lucila (2006)
The use of new technologies does not mean that the applied education model is modern. New technologies can be used in a way that follows the traditional education model, with all its deficiencies. The collaborative education model involves students in reflection, participation, and construction of their knowledge, or to collaboratively learn. This article aims to present mechanisms to stimulate collaborative learning, in present education, through the aid of virtual learning environments.